Clear Aligner Treatments in Orthoperio Patients - Gianluca Mampieri; Roberta Condò; Giovanni Di Caccamo; Paola Pirelli; Aldo Giancotti (Case Reports in Dentistry)
Introduction. Orthodontic treatment is a recognized approach to support specific periodontal issues thanks to its capability to manipulate periodontal tissues. This concept is certainly not new, but the use of aligners in certain clinical conditions can be considered as being innovative when a multidisciplinary treatment is necessary. Moreover, aligners enable to plan 3D tooth movements, root placement, staging, and range of dental movements, alongside the improvement of oral hygiene. Thus, aligners can be suitable for the treatment of periodontal issues. In this article, the authors present two clinical cases with different periodontal issues: one with superficial periodontal problems and the other with a deep one. Both cases were successfully treated with aligners, highlighting how this invisible and comfortable tool can simplify the management of complex adult treatments. Conclusion. Digital workflow is the key for success in the aligner technique. The possibility to design a virtual plan of treatment and to transfer it in the real clinical world represents a way to limit errors and to reduce the time of orthodontic therapy.